Self-Perception on the Institutionalized Elderly Need of Dental Prosthesis - Arlete Maria Gomes Oliveira; Joana Danielle Brandão Carneiro; Glaucia Maria Bovi Ambrosano; Marcelo de Castro Meneghim (Association of Support to Oral Health Research (APESB), 2022)
Objective: To make an association between self-perception and the implementation of sociodemographic variables for the autonomous and / or partially dependent individuals in nursing homes. Material and Methods: Epidemiological, observational and cross-sectional study. The sample consisted of 208 institutionalized elderly, both sexes, 60 years old or older, independent or partially dependent, randomly selected from two long-term residential institutions. Subjective evaluation: self-perception questionnaire, Geriatric Oral Health Assessment Index, quality of life assessment, Oral Impacts on Daily Performance (OIDP), oral health self-assessment (OH) and the need for dental prostheses. Bivariate analysis, chi-square test and multiple logistic regression were used, with the variables with p<0.05 remaining in the model. Results: Men were edentulous (53.43%), 68.75% used some type of denture, and 64.91% required dental prostheses, 60.58% self-assessed (OH) as good / excellent; who reported a need for dental prostheses presented 6.7 times (95% CI: 3.2-14.3) and more likely to have an impact on OIDP, those who needed prosthetics had a 2.8 times chance (95% CI: 1.3-6.1) (p<0.0001). The self-reported need for prostheses was associated with prevalence severity of impacts on QoL, eating, pronounce words correctly, Smile without feeling embarrassed; and the main reasons for not having badly adjusted teeth / dentures. Conclusion: The institutionalized elderly self-perceive the need for dental prostheses, but it does not have a negative impact on quality of life.